Diagnosis and management of acute lower gastrointestinal bleeding: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Triantafyllou, Konstantinos; Gkolfakis, Paraskevas; Gralnek, Ian M.; Oakland, Kathryn; Manes, Gianpiero; Radaelli, Franco; Awadie, Halim; Camus Duboc, Marine; Christodoulou, Dimitrios; Fedorov, Evgeny; Guy, Richard J.; Hollenbach, Marcus; Ibrahim, Mostafa; Neeman, Ziv; Regge, Daniele; Rodriguez de Santiago, Enrique; Tham, Tony C.; Thelin-Schmidt, Peter; van Hooft, Jeanin E. (Endoscopy, 2021)
1 ESGE recommends that the initial assessment of patients presenting with acute lower gastrointestinal bleeding should include: a history of co-morbidities and medications that promote bleeding; hemodynamic parameters; physical examination (including digital rectal examination); and laboratory markers. A risk score can be used to aid, but should not replace, clinician judgment.Strong recommendation, low quality evidence.2 ESGE recommends that, in patients presenting with a self-limited bleed and no adverse clinical features, an Oakland score of ≤ 8 points can be used to guide the clinician decision to discharge the patient for outpatient investigation.Strong recommendation, moderate quality evidence.3 ESGE recommends, in hemodynamically stable patients with acute lower gastrointestinal bleeding and no history of cardiovascular disease, a restrictive red blood cell transfusion strategy, with a hemoglobin threshold of ≤ 7 g/dL prompting red blood cell transfusion. A post-transfusion target hemoglobin concentration of 7–9 g/dL is desirable.Strong recommendation, low quality evidence.4 ESGE recommends, in hemodynamically stable patients with acute lower gastrointestinal bleeding and a history of acute or chronic cardiovascular disease, a more liberal red blood cell transfusion strategy, with a hemoglobin threshold of ≤ 8 g/dL prompting red blood cell transfusion. A post-transfusion target hemoglobin concentration of ≥ 10 g/dL is desirable.Strong recommendation, low quality evidence.5 ESGE recommends that, in patients with major acute lower gastrointestinal bleeding, colonoscopy should be performed sometime during their hospital stay because there is no high quality evidence that early colonoscopy influences patient outcomes.Strong recommendation, low quality of evidence.6 ESGE recommends that patients with hemodynamic instability and suspected ongoing bleeding undergo computed tomography angiography before endoscopic or radiologic treatment to locate the site of bleeding.Strong recommendation, low quality evidence.7 ESGE recommends withholding vitamin K antagonists in patients with major lower gastrointestinal bleeding and correcting their coagulopathy according to the severity of bleeding and their thrombotic risk. In patients with hemodynamic instability, we recommend administering intravenous vitamin K and four-factor prothrombin complex concentrate (PCC), or fresh frozen plasma if PCC is not available.Strong recommendation, low quality evidence.8 ESGE recommends temporarily withholding direct oral anticoagulants at presentation in patients with major lower gastrointestinal bleeding.Strong recommendation, low quality evidence.9 ESGE does not recommend withholding aspirin in patients taking low dose aspirin for secondary cardiovascular prevention. If withheld, low dose aspirin should be resumed, preferably within 5 days or even earlier if hemostasis is achieved or there is no further evidence of bleeding.Strong recommendation, moderate quality evidence.10 ESGE does not recommend routinely discontinuing dual antiplatelet therapy (low dose aspirin and a P2Y12 receptor antagonist) before cardiology consultation. Continuation of the aspirin is recommended, whereas the P2Y12 receptor antagonist can be continued or temporarily interrupted according to the severity of bleeding and the ischemic risk. If interrupted, the P2Y12 receptor antagonist should be restarted within 5 days, if still indicated.Strong recommendation, low quality evidence.